2001
DOI: 10.1007/pl00000866
|View full text |Cite
|
Sign up to set email alerts
|

Transposase and cointegrase: specialized transposition proteins of the bacterial insertion sequence IS21 and related elements

Abstract: The bacterial insertion sequence IS21 shares with many insertion sequences a two-step, reactive junction transposition pathway, for which a model is presented in this review: a reactive junction with abutted inverted repeats is first formed and subsequently integrated into the target DNA. The reactive junction occurs in IS21-IS21 tandems and IS21 minicircles. In addition, IS21 shows a unique specialization of transposition functions. By alternative translation initiation, the transposase gene codes for two pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 125 publications
2
61
0
Order By: Relevance
“…In this view, the IS element FK1 co-transferred with nod genes to the recipient (Fig. 1B) belongs to the IS21 family 3,13,14) . A minicircle containing IS21 copies has been detected in preparations of plasmid DNA carrying IS21, raising the possibility that IS21 is transposed together with other DNA fragments via a circular intermediate 3) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this view, the IS element FK1 co-transferred with nod genes to the recipient (Fig. 1B) belongs to the IS21 family 3,13,14) . A minicircle containing IS21 copies has been detected in preparations of plasmid DNA carrying IS21, raising the possibility that IS21 is transposed together with other DNA fragments via a circular intermediate 3) .…”
Section: Discussionmentioning
confidence: 98%
“…1B) belongs to the IS21 family 3,13,14) . A minicircle containing IS21 copies has been detected in preparations of plasmid DNA carrying IS21, raising the possibility that IS21 is transposed together with other DNA fragments via a circular intermediate 3) . This together with the unstable behavior of the acquired nod genes during successive cultures, suggests the IS element FK1 forms a minicircle intermediate carrying nod genes.…”
Section: Discussionmentioning
confidence: 99%
“…Both IstA and IstB are required for efficient transposition whereas a product of an alternative translation initiation within the Tpase gene may facilitate integration. Using IstA-enriched Escherichia coli cell extracts, it was shown that this protein is responsible for 3′ end cleavage of IS21 and of both ends in the IR junction (177).…”
Section: Is21 (I) Generalmentioning
confidence: 99%
“…It has been suggested that covalently closed IS circles and dimers could be alternative representations of the same transpositional pathway (Lewis & Grindley, 1997;Kiss & Olasz, 1999). Recent studies (Berger & Haas, 2001;Prudhomme et al, 2002;Turlan et al, 2000) seem to further support this possibility.…”
Section: Discussionmentioning
confidence: 94%